EVALUATION OF ARABIC LANGUAGE TEXTBOOKS AT UIN SYARIF HIDAYATULLAH JAKARTA - Ahmad Royani; Mukhson Nawawi; Maswani Maswani (Abjadia : International Journal of Education, 2020)
This research was conducted with the aim of describing the level of compatibility of Arabic language textbooks at UIN Syarif Hidayatullah Jakarta with the general purpose of learning Arabic. This research is a descriptive  and non-interactive study. The research method used is the content analysis, because in this study the contents of the textbooks in Arabic was analyzed The results of the study show that in general the books evaluated have been good and decent enough to be used as book dars, except that there needs to be an adjustment in terms of material content. In terms of the completeness, breadth and depth of the material, it appears that the book al-arabiyyah bi annamadziz, al-arabiyyah li tullabil jamiah, and the Arabic language of the Quran, make Arabic material complete, detailed, and profound which is gradually adjusted to the level of marhalah. In terms of material accuracy, these books contain grammatical and accurate terms In terms of the latest material, the book a al-arabiyyah bi annamadziz is considered not up-to-date.